An umpolung reaction of α-iminothioesters possessing a cyclopropyl group. Issue 17 (10th March 2020) - Shimizu, Makoto; Morimoto, Takayoshi; Yanagi, Yusuke; Mizota, Isao; Zhu, Yusong
Abstract : Tandem N -alkylation/oxidation/second addition reaction to α-cyclopropyl α-imino(thio)esters gave N -alkylated ring-opened products in good yields. Abstract : An umpolung N -alkylation reaction of α-cyclopropyl α-iminothioesters with diethylaluminum chloride or ethylmagnesium bromide affords the corresponding N -ethylated α-aminothioesters in good yields. Subsequent oxidation and reaction of the N -ethylated product with a thiolate or a chloride anion proceed effectively to give the ring-opened products in good yields. In contrast, relatively "hard" nucleophiles did not give the ring-opened products but gave the addition products to the iminium carbon.